Ecotourism as a medium of promotion and learning Japanese traditional culture - Tribuana Tunggadewi Kusumowardhani Baiquni; Reny Wiyatasari (Universitas Ahmad Dahlan, 2023)
After going through the pandemic for approximately two years, the enthusiasm of foreign tourists to come to Japan would still high. This proves that tourism is the leading sector of foreign exchange for Japan. Apart from being a foreign exchange, Japan can also promote the uniqueness of their country, including Japanese traditional culture. Japan promotes its traditional culture through one of the concepts of sustainable tourism, which is ecotourism. Ecotourism is not just an activity that prioritizes nature as an attraction but also aims to preserve the environment and improve the cultural welfare of the local community. This study explains the role of ecotourism as a medium for promoting and learning Japanese traditional culture. The method used in this study is a qualitative descriptive method. The results of this study indicate that Japan can promote ecotourism and its traditional culture with collaborations between the stakeholders. Furthermore, tourists can learn about Japanese traditional culture through various activities offered by ecotourism destinations.